Immunohistochemical Expression of AQP2 and HSP70 in Broiler Kidney Tissue Treated with Salix tetrasperma Roxb. Extract under Heat Exposure - Sugito Sugito; Etriwati Etriwati; Muslim Akmal; Erdiansyah Rahmi; Mira Delima; Zainal Abidin Muchlisin; Denny Irmawati Hasan (The Scientific World Journal)
The administration of plant extracts to broilers may be a way to mitigate the effects of heat stress. The importance of AQP2 and HSP70 compounds in maintaining the homeostasis of the chicken body when it is subjected to heat stress is well established. This study aims to determine the effect of giving the ethanolic extract of the leaves of Salix tetrasperma Roxb. on the immunohistochemical expression of AQP2 and HSP70 in exposed and unexposed broiler kidney tissue. This study used 36 samples of 28-day-old chicken kidneys. Chickens were kept in individual cages, provided with feed and drinking water ad libitum. The design used was a completely randomized design with 6 treatments and 6 replications: (a) chickens were reared in conditions exposed to heat (HS + 0); (b) chickens were reared in conditions exposed to heat and given Salix extract at a dose of 50 mg/L drinking water (HS + 50); (c) chickens were reared under heat-exposed conditions and given Salix extract at a dose of 100 mg/L drinking water (HS + 100); (d) chickens were reared in conditions without exposure to heat (n-HS + 0); (e) chickens were reared in conditions without exposure to heat and given Salix extract at a dose of 50 mg/L drinking water (nHS + 50); and (f) chickens were reared in conditions exposed without exposure to heat and given 100 mg/L drinking water (nHS + 100) of Salix extract. Salix extract was given for 24 hours and was renewed every 6 hours. The results showed that giving Salix extract 100 mg/L in drinking water to chickens exposed to heat (HS + 100) reduced the value of the H/L ratio. Giving Salix extract 50–100 mg/L in drinking water caused an upregulated AQP2 expression; on the other hand, it downregulated HSP-70 expression, in chicken kidney tubules both exposed to heat stress and nonexposed to heat stress. In conclusion, exposure to heat stress in broiler chickens and giving Salix extract can increase the formation of aquaporin 2 compounds and suppress the formation of HSP70.